Leadership Styles of the Professionals from the National Agricultural Research and Education System (Indian Journal of Extension Education, 2021)
Leadership style impacts others in shared directions and important resource of all organizations. Due to differences in goals, training, experiences, and methodologies between various groups, differences may exist in their leadership styles, style ranges, and style adaptabilities. The Leader Effectiveness and Adaptability Description (LEAD) instruments contains twelve leadership situations in which respondents are asked to select four alternative actions-a high task/low relationship behaviour, a high task/high relationship behaviour, a high relationship/low task behaviour, and a low relationship/low task behaviour- the style at respondents felt would most closely describe their behaviour in that type of situation. The study examines the leadership styles of professionals engaged in the national agricultural research and education system which consists of ICAR and SAUs. Data from 560 professionals working in the NARES at different cadres was collected. Most of the professionals were found to be having selling style of leadership followed by telling style. From the Fisher’s exact test for association, it was found that the none of the variables have any close association with their leadership style.